Process Dynamic of Two-Thermal-Tank-Series with Dead Time - Yulius Deddy Hermawan; Wibiana Wulan Nandari; Fauzan Irfandy; Riski Ajin Rahmadi; Aryandhanu Mukti Tri Perkasa (Eksergi, 2020)
The multi-tank-series system could come up the problem of instability due to dead-time. The goals of this work are to study the dynamic behavior of Two-Thermal-Tanks-Series (TTTS) with dead time through the open loop experiment in laboratory, and to propose the new-module of fundamental chemical engineering practicum in field of process dynamic for undergraduate program. The two stirred-tank-heaters @10L were designed for heating of water fluid. Both of tanks were designed overflow to maintain their volume constant. The gate valve was installed in the inlet pipe of Tank-1 to adjust its volumetric flowrate (f). The inlet temperature of Tank-1 (T1), the liquid temperatures in Tank-1 (T2) and Tank-2 (T3) were measured by thermocouple multi-channels. The volt-ampere-regulators were used to adjust the electrical energy in Tank-1 (q1) and Tank-2 (q2). The mathematical model was solved and rigorously examined in Xcos/Scilab. In order to study the dynamic behavior of TTTS, the inlet flowrate disturbance was made based on step input change. According to our investigation in laboratory and open loop simulation, both Tank-1 and Tank-2 gave stable responses, the model’s responses showed the closed and similar trend with laboratory’s responses, and time delay of about 30 seconds has been found in Tank-2.